COMPARATIVE ANALYSIS OF ATTITUDES AND PERCEPTIONS ABOUT RAPE AMONG MALE AND FEMALE UNIVERSITY STUDENTS - Kamal, Anila; Shaikh, Irshad Ali; Shaikh, Masood Ali (Journal of Ayub Medical College Abbottabad, 2010)
Background: Rape and other forms of violence against women have been reported to be common in Pakistan, and police is often reluctant to register a rape complaint. We assessed and compared the attitudes and perceptions of male and female university students towards rape of females by males. Methods: A cross-sectional survey with convenience sampling was conducted among the male and female students of Quide-e-Azam University, Islamabad. A structured, self-administered, anonymous and pre-tested questionnaire was used with close-ended questions. Students were asked about their attitudes and beliefs regarding characteristics of the female rape victims, male perpetrators and contexts in which this type of violence is more or less likely. Interviewers approached conveniently-selected participants and explained the objectives of the survey, while emphasising voluntary participation in this study. Data was analysed for frequencies and counts, while Chi-square test was used to for pairwise comparisons between male and female students with STATA 9. Results: Five hundred and four students, 247 male and 257 female, completed the questionnaire. Male students were more likely to believe that strong character of a woman would ostensibly shield her from the advances of a rapist; only young and pretty women get raped; woman’s willingness is present in rape. About 25% of students also believed that a raped woman is not worthy of becoming another man’s wife. One third of students believed that there could be no rape in marital context. Conclusion: Rape myths were common in our educated study respondents with significant gender differences. Attitudes and beliefs blaming the female victim of rape were more common in males. Keywords: Rape, Attitudes, University Students, Pakistan